PENGARUH KOMPETENSI DAN AMBIGUITAS PERAN TERHADAP KINERJA YANG DIMEDIASI KOMITMEN ORGANISASIONAL ( Studi pada SKPD Kecamatan Pekalongan Selatan ) - Muchamad Natsir, 12.5202.0148 (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of writing is to analyze and describe the effect of competency and role ambiguity on organizational commitment. In addition, to analyze and describe the influence of competence, role ambiguity and organizational commitment on performance of employees in South Pekalongan districts. Recent result research can be conclude that : (1). Competence has no effect on organizational commitment (2), the ambiguity of role no effect on organizational commitment (3). Competence significant positive effect on performance (4). Ambiguity of role significant negative effect on performance (5). Organizational commitment has no effect on performance, organizational commitment is thus not mediate the effect of competence and role ambiguity on performance. Keywords: Competence, Role Ambiguity, Organizational Commitment and Performance.